Clinical management of resistance evolution in a bacterial infection: A case study. Issue 1 (10th October 2015) - Woods, Robert J.; Read, Andrew F.
Abstract : This chronic bacterial infection evolved extensive resistance, killing the patient. Evolutionary science is insufficiently developed to better manage such life-threatening evolution. Abstract : We report the case of a patient with a chronic bacterial infection that could not be cured. Drug treatment became progressively less effective due to antibiotic resistance, and the patient died, in effect from overwhelming evolution. Even though the evolution of drug resistance was recognized as a major threat, and the fundamentals of drug resistance evolution are well understood, it was impossible to make evidence-based decisions about the evolutionary risks associated with the various treatment options. We present this case to illustrate the urgent need for translational research in the evolutionary medicine of antibiotic resistance.